Historitas Studi Islam - Hikmah, Nurul; Anisa Vira; Norafnan, Abdul (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
The purpose of this research is to find out the historical approach in Islamic studies. The research method used is a qualitative method with the type of library research or library research, namely sourced from the works of the library, whether in the form of scientific articles, books, and so on. Of course, this research is expected as education and literacy for readers. Remembering this historical approach is very important in understanding religion, because religion itself descends from concrete situations and is related to social conditions. With this approach we will be shown the actual state of an event. Someone who wants to study a deeper understanding of the Qur'an or the events that accompanied the revelation of the Qur'an needs to be equipped with a historical approach to Islamic studies. The purpose of using the historical approach is to reconstruct past events objectively and systematically, by collecting, verifying, evaluating, and synthesizing evidence to explain the facts so that strong conclusions can be obtained. The results of this literature review show that, the large number of Muslims who only know Islamic texts but do not know how it relates to history and life in society indicates the need for an approach and methodology that explores the relationship between texts and human experience and culture through a historical approach. By taking a historical approach, a reviewer will be shown the actual situation regarding an event related to Islamic studies.